Pengaruh Pendapatan Asli Daerah (PAD) Dan Dana Alokasi Umum (DAU) Serta Analisis Flypaper Effect Pada Belanja Daerah - Fahriani Fahriani; Ruddy Syafrudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of Regional Original Revenue (PAD) on Regional Expenditure and the effect of the General Allocation Fund (DAU) on Regional Expenditure in districts/cities in Central Kalimantan and find out whether there is a flypaper effect on District / City Regional Spending in Central Kalimantan in 2016 -2018. The objects in this study are all regencies/cities in Central Kalimantan. This study uses secondary data from the Realization of Regional Revenue and Expenditure Budget Report in the District/city Government in Central Kalimantan Province in 2016-2018. The data analysis method used is the multiple linear regression analysis methods.              The results of this study indicate that: (1) Regional Original Revenue (PAD) partially does not affect Regional Expenditure in Regency / City in Central Kalimantan Province from 2016-to 2018 because the probability value is 0.4656> 0.05. While the General Allocation Fund (DAU) partially has a significant positive effect on Regional Expenditure in the Districts / Cities in Central Kalimantan from 2016-to 2018 because the probability value is 0.0000 <0.05. (2) PAD and DAU simultaneously have a significant positive effect on Regional Expenditures, and the results are that the flypaper effect phenomenon occurs.